2010
DOI: 10.5194/amt-3-1063-2010
|View full text |Cite
|
Sign up to set email alerts
|

High time-resolution chemical characterization of the water-soluble fraction of ambient aerosols with PILS-TOC-IC and AMS

Abstract: Abstract.A particle-into-liquid sampler (PILS) was coupled with a total organic carbon analyzer (TOC) and two ion chromatographs (IC) to enable high time-resolution measurements of water-soluble ions and water-soluble organic carbon (WSOC) by a single sampling and analytical setup. The new high time-resolution measurement system, the PILS-TOC-IC, was able to provide essential chemical and physical information about fast changes in composition, concentrations and likely sources of the water-soluble fraction of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 55 publications
0
51
1
1
Order By: Relevance
“…An extensive review of the previously reported PILS campaigns has been presented in Timonen et al (2010), where the principle of the PILS was also given. The schematic diagram of the sampling system and the analysis apparatus used in the present study is presented in Fig.…”
Section: Sampling With Pilsmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive review of the previously reported PILS campaigns has been presented in Timonen et al (2010), where the principle of the PILS was also given. The schematic diagram of the sampling system and the analysis apparatus used in the present study is presented in Fig.…”
Section: Sampling With Pilsmentioning
confidence: 99%
“…PILS enables the online analysis of the collected samples with several analytical devices, such as ion chromatographs (IC), analyzers for water-soluble organic carbon (WSOC), or liquid wavelength capillary cell and absorbance spectrophotometry (e.g., Orsini et al, 2003;Sullivan et al, 2004;Rastogi et al, 2009;Timonen et al, 2010). Also an application of the online coupling of the PILS with a solid-phase extraction to liquid chromatography-mass spectrometry has been presented for the analysis of organic acids in aerosols (Parshintsev et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The description of HR-ToF-AMS is available in previous publications (DeCarlo et al, 2006;Timonen et al, 2010;Huang et al, 2011). A PM 1 cyclone was used as the AMS inlet to remove coarse particles and introduced sampled air into the instrument through a copper tube with a flow rate of 10 l min −1 and the AMS sampled isokinetically from the center of the copper tube at a flow rate of 80 ml min −1 .…”
Section: Field Comparison Of Aerosol Species In Changdaomentioning
confidence: 99%
“…Inside the PILS aerosols grow continuously in an environment that is supersaturated by generating water vapor. A 0.05-ppbv lithium bromide solution (Sigma Aldrich, USA) was pumped into the head of the PILS at 0.37 mL min -1 as the internal standard for calculating the dilution factor (Timonen et al, 2010). The dilution factor ranged from 1.0 to 1.3 for the entire experiment (Appendix 1).…”
Section: Methodsmentioning
confidence: 99%